AN INTERPRETATION OF THE CHANGES OBSERVED IN V1057 CYGNI - PISMIS, P (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1972)
It is argued that the brightening of V1057 Cygni, a T-Tauri star, roughly from photographic magnitude 15.5 to 10.0 and its change of spectral type from about KO to A1, at which the star appears to remain, may be explained by a fast readjustment of mass di
BOL OBS TONAN TACUB
Keywords: INTERPRETATION, CHANGES, OBSERVED; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS